ISOLATION AND STUDY OF MYELOPEROXIDASE AND GLUTAMATE DEHYDROGENASE ENZYMES FROM TUMOR PULMONARY TISSUE - M. Fakhri, Mahmmood A.; Hammo, Raghad A. M. (International Journal of Psychosocial Rehabilitation, 2020)
The research included the isolation of Myeloperoxidase and Glutamate Dehydrogenase from tumor lung tissue using different biological techniques. These techniques included: ammonium sulfate precipitation, dialysis, gel filtration chromatography on sephadex G–200. For partially purified Myeloperoxidase, The results showed that specific activity and the number of fold of purification were (42.59 U/ml) and (36.3), respectively. On the other hand, the results showed that specific activity and the number of fold of purification for partially purified Glutamate Dehydrogenase were (22.69 U/ml) and (44.1), respectively. Furthermore, using gel filtration chromatography, the comparative molecular weights of the partially isolated Myeloperoxidase and Glutamate Dehydrogenase was (150.3 kDa) and (332.3 kDa), respectively. The study showed that the optimum conditions of Myeloperoxidase were obtained at the first minute using sodium citrate (0.1 M), as buffer at pH (5.5), at a temperature (45 ºC) and (14 mM) of ο-dianisidin as substrate. It was found that Vmax and Km have the values of (18.86 U/ml) and (2,69 mM), respectively. Finally, The optimum conditions of Glutamate Dehydrogenase were obtained using Tris-HCl (100 mM) as a buffer, at pH (8.6), at a temperature (40 C°) and (35 mM) of glutamate as a substrate. It was found that Vmax and Km have the values of (14.1 U/ml) and (16.56 mM) respectively.